2009
DOI: 10.1016/s0140-6736(09)61258-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intermittent preventive treatment with sulfadoxine-pyrimethamine for malaria in African infants: a pooled analysis of six randomised, placebo-controlled trials

Abstract: Bill & Melinda Gates Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
201
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(214 citation statements)
references
References 45 publications
12
201
0
1
Order By: Relevance
“…The WHO therefore recommends IPTp with SP for areas with high or moderate transmission, and many countries have substantially scaled up delivery of IPTp, although coverage is still inadequate (van Eijk et al, 2011). IPTi has been shown to be safe in infants, with a protective efficacy of~30 % against clinical malaria and 21 % against the risk of anaemia from the first dose until 12 months of age (Aponte et al, 2009). Unfortunately, levels of SP resistance are on the rise in many areas, requiring adaptation of SP regimes.…”
Section: Drug Applications For Prevention Of Malaria In Endemic Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO therefore recommends IPTp with SP for areas with high or moderate transmission, and many countries have substantially scaled up delivery of IPTp, although coverage is still inadequate (van Eijk et al, 2011). IPTi has been shown to be safe in infants, with a protective efficacy of~30 % against clinical malaria and 21 % against the risk of anaemia from the first dose until 12 months of age (Aponte et al, 2009). Unfortunately, levels of SP resistance are on the rise in many areas, requiring adaptation of SP regimes.…”
Section: Drug Applications For Prevention Of Malaria In Endemic Areasmentioning
confidence: 99%
“…Unfortunately, this effect has not been reproduced in later studies. In some occasions, even a small increase in malaria incidence was observed after cessation of the intervention (Konaté et al, 2011;Mockenhaupt et al, 2007) but, as was the case for chemoprophylaxis, most studies did not show a change in malaria incidence after the end of the intervention (Aponte et al, 2009;Cairns et al, 2008;Cissé et al, 2006;Dicko et al, 2011;Schreiber et al, 2007).…”
Section: Clinical Rebound After Chemoprophylactic Interventionsmentioning
confidence: 99%
“…It was concluded that IPTi is safe and does not interact with EPI vaccines. Importantly, IPTi had a pooled protective efficacy of 30.3% (95% CI 19.8-39.4, p<0.0001) [24].…”
Section: Sulfadoxine-pyrimethamine and Inter-mittent Preventive Treatmentioning
confidence: 95%
“…However, it is still being recommended for the intermittent preventive treatment of malaria in pregnancy inmalarious areas. Further it is being evaluated for the same in infants (Aponte et al, 2009). Proguanil as a single agent, on one hand, has been found to be effective against chloroquine and pyrimethamine-sulfadoxine resistant strains of P. falciparum found in sub-Saharan Africa.…”
Section: Anti-folatesmentioning
confidence: 99%